PENGEMBANGAN MODEL CREDIT SCORING UNTUK PROSES ANALISIS KELAYAKAN USAHA PARA ANGGOTA KOPERASI SIMPAN PINJAM DI KABUPATEN SRAGEN (STUDI KASUS KSP DAN USP) - Jumingan, Jumingan (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2015)
AbstractResearch objectives are: (1) To measure the accuracy of credit scoring models currently applied in the assessment KSP / USP in assessing the feasibility of small business for the cooperative members in a potential borrower; (2) To determine the parameters applied in credit ratings for assessing the cooperative members on the feasibility of members of the potential borrower; (3) To determine the value assessment and credit scoring models to assess the feasibility the business facilities KSP member (4) To design a model of credit scoring for small business feasibility analysis facilities of potential borrowers: The results of the analysis the validity of the model by using the ROC Curve analysis showed that the parameters have a significant effect yet fully demonstrated the contribution expected for the level of sensitivity and specification as reflected by the low value of the ROC Curve. The validity of the scoring model E-flow KSP not optimal feasibility analysis of the expected yield on each proposed facility KSP. Due to the fact that there is still a low level of validity of the valuation models, it is necessary to make efforts to formulate improvement scoring model to be applied in the analysis KSP feasibility analysis on the parameters adopted in the scoring model E-flow has resulted in 15 parameters, namely: interest rate , insurance number, age, occupation, pay monthly, monthly income, average balance, a savings bank, the percentage down payment, type of mortgage, ownership documents, or limit the size of the building, the ratio of debt burden, information about debt maturities, operational marketing , Operational employees, employee fraud, 5C and position requirements/job anggota: In addition to designing models for credit scoring application, is also being considered that this model would be more appropriate if the points of prepayment behavior score and scoring included. Keywords: Credit Scoring Model. KSP / USP